Polymorphisms in Th1/Th2 Cytokine Genes, Hormone Replacement Therapy, and Risk of Non-Hodgkin Lymphoma - Zhu, Gongjian; Pan, Dongsheng; Zheng, Tongzhang; Lan, Qing; Chen, Xuezhong; Chen, Yingtai; Kim, Christopher; Bi, Xiaofeng; Holford, Theodore; Boyle, Peter; Leaderer, Brian; Chanock, Stephen; et al. (Frontiers in Oncology, 2011)
We conducted a population-based case–control study in Connecticut women to test the hypothesis that genetic variations in Th1 and Th2 cytokine genes modify the relationship between hormone replacement therapy (HRT) and risk of non-Hodgkin lymphoma (NHL). Compared to women without a history of HRT use, women with a history of HRT use had a significantly decreased risk of NHL if they carried IFNGR2 (rs1059293) CT/TT genotypes (OR = 0.5, 95%CI: 0.3–0.9), IL13 (rs20541) GG genotype (OR = 0.6, 95%CI: 0.4–0.9), and IL13 (rs1295686) CC genotype (OR = 0.6, 95%CI: 0.4–0.8), but not among women who carried IFNGR2 CC, IL13 AG/AA, and IL13CT/TT genotypes. A similar pattern was also observed for B-cell lymphoma but not for T-cell lymphoma. A statistically significant interaction was observed for IFNGR2 (rs1059293 Pfor interaction = 0.024), IL13(rs20541 Pfor interaction = 0.005), IL13 (rs1295686 Pfor interaction = 0.008), and IL15RA (rs2296135 Pfor interaction = 0.049) for NHL overall; IL13 (rs20541 Pfor interaction = 0.0009), IL13(rs1295686 Pfor interaction = 0.0002), and IL15RA (rs2296135 Pfor interaction = 0.041) for B-cell lymphoma. The results suggest that common genetic variation in Th1/Th2 pathway genes may modify the association between HRT and NHL risk.